Sonic Hedgehog promotes in vitro oocyte maturation and term development of embryos in Taiwan native goats - Wang, De-Chi; Huang, Jan-Chi; Lo, Neng-Wen; Chen, Lih-Ren; Mermillod, Pascal; Ma, Wen-Lung; Chiang, Hsin-I.; Ju, Jyh-Cherng (Theriogenology, 2017)
The aim of this study was to investigate the effects of Shh (Sonic Hedgehog) protein on caprine oocyte maturation, early embryo development, and developmental competence after embryo transfer of vitrified-thawed in vitro-produced embryos. Cumulus-oocyte complexes (COCs) derived from abattoir were randomly allocated to the in vitro maturation (IVM) medium supplemented with 0 (Control), 0.125, 0.25, 0.5, or 1.0 μg mL−1 recombinant mouse Shh protein. After IVM, COCs were fertilized with frozen-thawed semen and the presumptive zygotes were cultured on goat oviduct epithelial monolayers in M199 medium for 9 days. Our results showed that supplementation of Shh (0.25 or 0.5 μg mL−1) enhanced oocyte maturation as compared with the control group (92.4% and 95.0% vs. 86.2%, P < 0.05), yet the effect could be reversed by the simultaneous addition of cyclopamine (an inhibitor of Shh signaling by direct binding to the essential signal transducer Smo). Subsequently, an improved blastocyst rate (66.3 ± 10.9, P < 0.05) was observed for the embryos derived from the oocytes matured in the presence of 0.5 μg mL−1 Shh compared with the control group (41.4 ± 12.9). Expressions of Shh, SMO and Gli1 were observed in the ovaries, granulosa cells, COCs, cumulus cells, oocytes and oviduct epithelia. Notably, Ptch1 was expressed in nearly all of the aforementioned tissues and cells except cumulus cells. The embryos exhibited a higher survival rates in the Shh-supplemented group (37.5%) compared to those without Shh supplementation (14.8%; P < 0.05) after embryo transfer. This study demonstrated the beneficial effects of Shh supplementation on oocyte maturation and subsequent embryo development both in vitro and in vivo, suggesting a functional existence of Shh signaling during the final stage of folliculogenesis and early embryogenesis in caprine. •Effects of Shh on oocyte maturation and embryo development of Taiwan Native Goats were examined.•Both in vitro and in vivo development are improved by an initial addition of Shh in maturation medium.•Functional Shh signaling during oocyte maturation and early embryogenesis exists in caprine.